CADASIL or NOTCH3 mutaion spectrum diseases? Interpretation of NOTCH3 mutations and clinical heterogeneity in CADASIL - Wang, Yuehui; Liu, Yiran; Mo, Hongbin; Han, Yue; Jing, Yuanyuan; Deng, Fang (Frontiers in Neurology, 2025)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an autosomal dominant disorder characterized by midlife-onset cerebrovascular disease and dementia. It is caused by mutations in the NOTCH3 gene, which affects the amount of cysteine in the extracellular domain (ECD) of the receptor, leading to protein misfolding and receptor aggregation. Emerging evidence indicates that beyond classical missense mutations, other variants including cysteine-sparing missense mutations, homozygous mutations, small deletions, duplications, splice site mutations, a deletion/insertion and loss-of-function mutations may lead to distinct phenotypes with variable severity and disease penetrance. The marked heterogeneity in genotypes and phenotypes poses significant challenges for CADASIL diagnosis and clinical management. The aim of this review is to summarize the mutational spectrum of CADASIL, explore the possible genotype–phenotype correlations and discuss the phenotypic heterogeneity of NOTCH3 mutations. More studies are needed in the future to demonstrate whether CADASIL can be expanded from classical cerebral small vessel disease to a new spectrum of diseases that share the same pathogenesis as mutations in the NOTCH3 gene.